Enclaves of freedom. On „second circulation” publishing in the PRL - Tatarowski, Konrad W. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
„Second circulation publishing”, the broadly defined publishing and cultural movement, independent of the authorities of the PRL and not subject to state censorship, was initiated in the autumn of 1976 by the community which opposed communist party rule in Poland. The author of the article offers a synthesis defining the notion of „second circulation”, indicating its scope of influence and its reach, discussing its significance at the levels of community, cultural and political life, and its influence on the democratic changes in Poland and other Central and East European states in the late-1980s.